Unveiling the oxidative stability, phytochemical richness, and nutritional integrity of cold-pressed Linum usitatissimum oil under UV exposure - Oumayma Belhoussaine; Chaimae El Kourchi; Amakhmakh Mohammed; Adil EL Yadini; Riaz Ullah; Zafar Iqbal; Khang Wen Goh; Monica Gallo; Hicham Harhar; Abdelhakim Bouyahya; Mohamed Tabyaoui (Food Chemistry: X)
This study examines the effect of UV irradiation on the oxidation stability of Linum usitatissimum oil, presenting possible changes in the phytochemical profile due to photo-oxidation. GC–MS analysis of the oils identified 11 fatty acid compounds with a high percentage of unsaturated fatty acids, the most important of which is α-linolenic acid (ALA), known as omega-3 (48.88 %), also significant profiles of phytosterol and tcocopherol isomers rich in β-Sitosterol and γ-tocopherols respectively. As well as physicochemical properties such as free fatty acids (FFA %), peroxide value (PV) and iodine value (IV), and nutritional indexes that determine the significant changes observed during the oxidation process, the most important of which is the progressive increase in acidity, peroxide, conjugated dienes and trienes and degrees of unsaturation over 8 h of UV exposure. High levels of carotenoids and phenolic compounds (TPC) protect and enhance oil quality in the face of irradiation, so a significantly small difference is observed between irradiated and non-irradiated oil during photo-oxidation.